2021
DOI: 10.1021/acsomega.1c02635
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nonwoven Carbon Tissue-Reinforced Epoxy Resin Adhesive Layer on the Single Lap Bonding Strength of Aluminum Alloy Joints

Abstract: The present paper provides a solution to enhance the reliability of bonding. The effect of the nonwoven carbon tissue (NWCT) composite adhesive layer on the bonding strength and reliability of aluminum alloy of single lap joints (SLJ) was investigated by embedding NWCT into the epoxy adhesive layer. The bonding strength, Weibull distribution, metallography of cross section, and fracture surface morphology of NWCT specimens were investigated. The results showed that the average bonding strength and Weibull char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Consequently, the reaction conversion decreases, resulting in a residue of unreacted substances at the interface, as evidenced by our previous study using X-ray photoelectron microscopy. 14,15 To improve the strength of epoxy adhesives to an adherend, reinforcement with fillers 16,17 and modification of the adherend surface 18−20 produce a hydroxy group, and the generated secondary amine further reacts with another epoxy group to form a tertiary amine, again producing a hydroxy group. This reaction mechanism indicates that the material becomes hydrophilic as the reaction proceeds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the reaction conversion decreases, resulting in a residue of unreacted substances at the interface, as evidenced by our previous study using X-ray photoelectron microscopy. 14,15 To improve the strength of epoxy adhesives to an adherend, reinforcement with fillers 16,17 and modification of the adherend surface 18−20 produce a hydroxy group, and the generated secondary amine further reacts with another epoxy group to form a tertiary amine, again producing a hydroxy group. This reaction mechanism indicates that the material becomes hydrophilic as the reaction proceeds.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the strength of epoxy adhesives to an adherend, reinforcement with fillers , and modification of the adherend surface by a chemical reaction and plasma treatment are effective. Considering amines as a curing agent, Figure shows the reaction scheme of epoxy and amine compounds.…”
Section: Introductionmentioning
confidence: 99%
“…What's more, in order to improve the result of Dupont test, the organic membrane, which can protect the single layer part from external force, was added in the process flow. Many reports indicated that resin may not only flatten the membrane but also protect from outer force because of its thickness and considerable elasticity [5]. The result of test was about twice higher than the samples without resin.…”
Section: Resultsmentioning
confidence: 92%
“…Epoxy adhesives have excellent mechanical properties, thermal properties, , adhesive properties, and electrical insulation properties, which have been widely used in packaging, construction, automotive, electronics, plastics, wood, and other fields. However, the slow curing rate of epoxy adhesives at room temperature and poor low-temperature resistance still limits their application in the field of electronic and electrical sealing, especially during the winter season.…”
Section: Introductionmentioning
confidence: 99%